2010
DOI: 10.1111/j.1740-8709.2010.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting micronutrient deficiencies among Sri Lankan pre‐school children: a community‐based study

Abstract: Assessing micronutrient status in children may also have the benefit of addressing the problems of various micronutrient deficiencies with a unified programmatic approach on a public health scale. A cross-sectional survey in the Galle district of the micronutrient and anthropometric status of 248 children of ages 3-5 years was performed to determine the prevalence of micronutrient deficiencies [iron, zinc (Zn), folate, calcium, caeruloplasmin, iodine, vitamin A and vitamin D] and the extent to which multiple m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…Prevalence of other micronutrient deficiencies (e.g. Folate) have been described among Sri Lankan children which may be a cause for anemia in this sample also [26, 45]. However, higher prevalence of iron deficiency was predicted by peripheral blood film analysis of the current sample.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Prevalence of other micronutrient deficiencies (e.g. Folate) have been described among Sri Lankan children which may be a cause for anemia in this sample also [26, 45]. However, higher prevalence of iron deficiency was predicted by peripheral blood film analysis of the current sample.…”
Section: Discussionmentioning
confidence: 62%
“…However, higher prevalence of iron deficiency was predicted by peripheral blood film analysis of the current sample. Higher prevalence of depleted iron stores in preschoolers and adolescents have been identified in other parts of the country [26, 45, 46]. Serum Ferritin depends on other factors such as presence of haemoglobinopathies [47] and inflammation [48].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is associated with micronutrient deficiencies [14,15]. Research has shown that supplementation to correct common micronutrient deficiencies such as iron, Vitamin A, Zinc or iodine deficiency is beneficial to children [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…There are only few studies available on vitamin D status of Sri Lankan children. VDD using a higher cut off value (< 35 nmol/l) was seen in 26% and 25% of male and female children respectively in the Southern province of Sri Lanka [11]. A Similar study done more recently revealed VDD (< 20 nmol/l) in 29% of study population [12].…”
Section: Potential Explanations For the Association Between Low 25(ohmentioning
confidence: 59%